PROFIL SUKU AKIT DI TELUK SETIMBUL KECAMATAN MERAL KABUPATEN KARIMUN KEPULAUAN RIAU - Syamsidar, Raja (Universitas Lancang Kuning, 2014)
The goal of this research is to describe The Profile of Aidt Tribe in Teluk Setimbul District Pasir Panjang Regency Meral Subdistrict Karimun, Riau Archipelago and social change that happens in society of Aidt Tribe in Teluk Setimbul District Pasir Panjang Regency Meral Subdistrict Karimun, Riau Archipelago. For analyzing data, the research is done quantitatively, the data collected is then explained descriptively namely describing or telling the research result with the logical sentence parsing so that it can be easy io understand. This research was done in Teluk Setimbul District Pasir Panjang Regency Mera! Subdistrict Karimun, RiauArchipelago. The result from the research shows that Aidt Tribe has experienced many changes that move forward, it can be seen from economic structure of Aidt Tribes society and custom of Akit Tribe now, where they have already changed and the changes can be seen from child s education, religion, means of livelihood, exogamy marriage, mobility that show different change from previous time.